THE MANUFACTURING OF SILICA GEL FROM BAMBOO LEAF ASH (Dendrocalamus asper (Schult. f) Backer ex Heyne) AND THE APPLICATION FOR ADSORPTION Cd (II) ION - -, Yasrin; -, Alimuddin; Panggabean, Aman Sentosa (JURNAL ATOMIK, 2020)
The research about silica gel manufacturing from bamboo leaf ash (Dendrocalamus asper (Schult.) Backer ex Heyne) and the application for Cd (II) ion adsorption has been done. The adsorption of Cd (II) ion done by some varieties, such as pH, concentration, and contact time. The result of the research showed the optimum pH was 8, the optimum concentration was 4 ppm and the contact time was 60 minutes. The adsorption capacity was 0.388 mg/g and the percentage of recovery was 93.44%.